THU0306 Predictors of outcome in a cohort of italian children/adolescents with primary raynaud's phenomenon: A multicenter study. (23rd January 2014) - Falcini, F.; Denaro, V.; Cuoco, F.; Martini, G.; Cappelli, S.; Petaccia, A.; Corona, F.; Carnesecchi, G.; La Torre, F.; Matucci Cerinic, M.; Rigante, D.
Abstract : Background: Raynaud's phenomenon (RP) is a benign reversible vasospasm of the extremities that may occur in the absence of any underlying connective tissue disease (CTD), mostly systemic lupus erythematosus, juvenile dermatomyositis and systemic scleroderma. Predictors of a favorable outcome are still unraveled in primary RP (pRP): the causative role of various autoantibodies remain to be elucidated mostly for pRP starting in childhood or adolescence. Objectives: To identify the possible predictors of outcome in a cohort of children and adolescents with pRP. Methods: We performed a prospective data collection of demographic, clinical, laboratory and treatment characteristics of 76 Italian children/adolescents with pRP (54 females, 22 males, median age at disease onset: 13.3 years, median age at diagnosis: 14.7 years), managed in 4 pediatric rheumatologic centres and 1 transition clinic during the last three years. Demographic characteristics included sex, age and ethnicity. The evaluation included clinical pictures, eventual disease associations, pubertal status, laboratory data and nailfold videocapillaroscopy (NVC) at baseline and at regular 6-month-follow-up. Laboratory examinations included erythrosedimentation rate, C-reactive protein, transaminases, creatinine, hemoglobin, complement fractions C4 and C3, renal and thyroid function and specific serum autoantibodies (anti-nuclear antibodies [ANA], anti-DNAds, anti-ENA, anti-cardiolipin, anti-Scl-70 and anti-centromere antibodies). Screening for coeliac disease was performed at the first evaluation. Treatment details included the eventual specific drug used, its dosage and overall treatment duration. Out of 76, 14 patients were treated with hydroxicloroquine, 10 with calcium blockers, 1 with low-dose aspirin, 3 with iloprost, while the remaining 48 did not receive any drug.A forward stepwise multiple logistic regression analysis was used to find any association among sex, pubertal status, inflammatory parameters, NVC abnormalities, all serum autoantibodies and the risk of developing a CTD at baseline and at 36-month-follow-up. The software used was STATA 10. A p -value <0.05 was considered significant Results: ANA positivity at baseline was significantly associated with the risk of developing a CTD ( p <0.05). No NVC abnormalities was related to specific patients' outcome. No patient resulted positive at the screening for coeliac disease. Conclusions: Our data show that only ANA positivity is the potential predictor of poor outcome and progression to CTD in children and adolescents with pRP. References: Nigrovic PA, Fuhlbrigge RC, Sundel RP. Raynaud's phenomenon in children: a retrospective review of 123 patients. Pediatrics 2003;111:715-21. Disclosure of Interest: None Declared